Controlled Synthesis and Visible-Light-Driven Photocatalytic Activity of BiOBr Particles for Ultrafast Degradation of Pollutants - Xiaohui Ji; Chen Li; Junhai Liu; Tianlei Zhang; Yue Yang; Ruijin Yu; Xuegang Luo (Molecules, 2023)
For the purpose of regulating the visible-light-driven photocatalytic properties of photocatalysts, we selected BiOBr as the research target and various routes were used. Herein, via the use of a hydrothermal method with various solvents, BiOBr particles with controllable morphology and photocatalytic activities are obtained. In particular, through changing the volume ratio of ethylene glycol (EG) to ethanol (EtOH), BiOBr compounds possess microspheres, in which samples synthesized by using EG:EtOH = 1:2 have the highest photocatalytic activity, and can completely decompose RhB under visible light irradiation within 14 min. Furthermore, we also used different volume ratios of EG and H2O reaction solvents to prepare BiOBr particles so as to further improve its pollutant removal ability. When the volume ratio of EG to H2O is 1:1, the synthesized BiOBr particles have the best photocatalytic activity, and RhB can be degraded in only 10 min upon visible light irradiation. Aside from the reaction solvent, the impact of sintering temperature on the photocatalytic properties of BiOBr particles is also explored, where its pollutant removal capacities are restrained due to the reduced specific surface area. Additionally, the visible-light-triggered photocatalytic mechanism of BiOBr particles is determined by h+, ·OH and ·O2− active species.